Reinvention of Tradition and Cultural Continuity of Shu Brocade in the Context of Chinese Modern Society: Aesthetic Innovation and Cultural Inheritance - Jing Zou,; Sirisuk, Metta (Journal of Roi Kaensarn Academi, 2023)
This research article explores the aesthetic innovation and cultural inheritance of Shu Brocade, a significant aspect of traditional Chinese culture, in the context of Reinvention of Tradition and modern societal changes. The study investigates the impact of modern societal changes on Shu Brocade, including shifts in societal functions, economic environments, and cultural perspectives. It also examines the aesthetic innovation of Shu Brocade in various artistic works, such as its application in painting, sculpture, and its fusion with contemporary art trends. Furthermore, the article highlights the cultural continuity of Shu Brocade, emphasizing its importance and value in modern society as a preserved cultural heritage and its contributions to the local economy and tourism industry. The education and promotion of Shu Brocade are discussed, focusing on the transmission of craftsmanship and its promotion in educational institutions and communities. Overall, this research underscores the significance of Shu Brocade in contemporary society and calls for further attention and research in this field.